Hepatic sarcoidosis with symptomatic portal hypertension: A report of 12 cases with review of the literature - Fauter, Maxime; Rossi, Geoffrey; Drissi-Bakhkhat, Ayoub; Latournerie, Marianne; Gerfaud-Valentin, Mathieu; Durieu, Isabelle; Jamilloux, Yvan; Bailly, François; Mahevas, Matthieu; Sève, Pascal (Frontiers in Medicine, 2022)
Introduction Sarcoidosis is a systemic granulomatosis of unknown etiology, characterized by the presence of immune granulomas. Liver damage is a relatively common extra-pulmonary manifestation, occurring in 3.6 to 30% of cases. Some patients can develop symptomatic portal hypertension. Few series have evaluated the prognosis of symptomatic portal hypertension as well as the efficacy and safety of specific treatment on this complication. Methods This is a multicenter retrospective study of cases of histologically proven hepatic sarcoidosis with symptomatic portal hypertension (ascites, digestive hemorrhage) and / or hepatic encephalopathy. Demographic characteristics, comorbidities, clinical manifestations of sarcoidosis, biological data, imaging study of the liver, treatment, and clinical outcomes were collected. Results Twelve patients were identified, with a mean follow-up of 140 months. The M / F ratio was 1 and Caucasian origin was the most represented (75%). Seven patients presented with hepatic comorbidities: metabolic syndrome, chronic alcoholism or chronic viral hepatitis. Apart from hepatic involvement, mediastino-pulmonary involvement was the most common followed by osteoarticular and skin. Liver damage was inaugural in two thirds of cases. Nine patients developed ascites and / or eight esophageal varices, six of which were complicated by gastrointestinal bleeding. One case of hepatic encephalopathy was observed. Five patients presented signs of hepatocellular insufficiency during follow-up, of whom three had hepatic comorbidities. Eight out of twelve patients required second-line treatment after failure of corticosteroids, three patients underwent ligation of esophageal varices but with recurrent digestive bleeding in all cases. Two patients benefited from a transjugular intrahepatic portosystemic shunt, also with poor result. At the end of follow-up, five patients were alive and seven patients died. Two patients received a liver transplant, with good result and without recurrence of sarcoidosis on the transplant thereafter. Two patients had quiet sarcoidosis on low dose of corticosteroids and one patient was lost to follow-up. Conclusion Symptomatic portal hypertension related to hepatic sarcoidosis is a severe complication, with high morbidity and mortality, and frequent failure of specific treatments of portal hypertension. Early management of these patients, with detection of hepatic comorbidities seems important. In case of therapeutic failure, liver transplantation is an option to consider.